A Prospective, Open-Label Study of Hyaluronic Acid-Based Filler With Lidocaine (VYC-15L) Treatment for the Correction of Infraorbital Skin Depressions. Issue 10 (October 2017) - Niforos, Francois; Acquilla, Raj; Ogilvie, Patricia; Safa, Marva; Signorini, Massimo; Creutz, Lela; Kerson, Graeme; Silberberg, Michael
Abstract : BACKGROUND: Infraorbital skin depressions are one of the most troublesome facial areas for aesthetically aware patients. OBJECTIVE: Evaluate effectiveness and safety of Juvéderm Volbella with Lidocaine (VYC-15L; Allergan plc, Dublin, Ireland) for correction of bilateral infraorbital depressions. METHODS: In this 12-month, prospective, uncontrolled, open-label study, subjects aged ≥18 years with infraorbital depressions rated ≥1 on the Allergan Infra-oRbital Scale (AIRS) received injections of VYC-15L with optional touch-up treatment on Day 14. The primary efficacy measure was ≥1 AIRS grade improvement from baseline at month 1. RESULTS: Of 80 subjects initially treated with VYC-15L, 75 (94%) completed the study. All injections were intentionally deep, most using multiple microbolus technique. At 1 month, 99.3% of eyes achieved ≥1 AIRS grade improvement. The responder rate (subjects with ≥1 AIRS grade improvement in both eyes) was 99% at month 1, 92% at month 6, and 54% at month 12. Most injection site reactions (e.g., bruising, redness, irregularities/bumps) were mild and resolved by day 14. Late-onset mild to moderate edema was observed in 11% of eyes at month 6% and 4% of eyes at month 12. CONCLUSION: VYC-15L is effective and safe for the treatment of infraorbital depressions, with effectiveness lasting up to 12 months.